2014
DOI: 10.1177/1541204014551805
|View full text |Cite
|
Sign up to set email alerts
|

The Unpredictability of Murder

Abstract: There is minimal research that has investigated the characteristics distinguishing youth who commit murder to other juvenile offenders. Of the research that has been done, scholars have identified a wide variety of factors that distinguish these offenders, including poor family environments, emotional and social problems, poor mental health, and behavioral disorders. Using data from Pathways to Desistance, a study of 1,354 serious youthful offenders, we examined how 8 demographic characteristics and 35 risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 75 publications
6
7
0
Order By: Relevance
“…In other words, clinical samples of youth evince a high preponderance of abusive experiences and deprivation. These findings were consistent with studies of youth residing in detention, correctional, and confinement facilities [7,8,9,10,11] where adverse childhood experiences are endemic.…”
Section: Introductionsupporting
confidence: 90%
“…In other words, clinical samples of youth evince a high preponderance of abusive experiences and deprivation. These findings were consistent with studies of youth residing in detention, correctional, and confinement facilities [7,8,9,10,11] where adverse childhood experiences are endemic.…”
Section: Introductionsupporting
confidence: 90%
“…Similarities observed allow disregard the hypothesis of significant association between psychopathic traits and juvenile homicidal behavior and reveal that vulnerability should be the focus for prevention efforts on both sides. This collectively homogeneous image is consistent with previous studies in Latin America (Wiese & Folino, 2009) and North America (DeLisi, Piquero, & Cardwell, 2016). In the study by DeLisi et al (2016), out of the 43 variables that covered three dimensions-individual, familial, and situational-authors found significant differences in only five variables of the bivariate analysis, and of these, only low IQ and the history of exposure to violence remained statistically significant when included into a logistic regression model.…”
Section: Discussionsupporting
confidence: 90%
“…This collectively homogeneous image is consistent with previous studies in Latin America (Wiese & Folino, 2009) and North America (DeLisi, Piquero, & Cardwell, 2016). In the study by DeLisi et al (2016), out of the 43 variables that covered three dimensions-individual, familial, and situational-authors found significant differences in only five variables of the bivariate analysis, and of these, only low IQ and the history of exposure to violence remained statistically significant when included into a logistic regression model. In addition to the concurrence in findings from that study and ours, it is interesting to note that both agree on the use of some measures-PCL-YV, WAI, RPI-and in the absence of significant differences in such variables between the groups.…”
Section: Discussionsupporting
confidence: 90%
“…Individual-level risk factors among juvenile homicide offenders have included a history of violent offending prior to the homicide offense [13,20], as well as educational deficits and alcohol abuse (in retrospective comparisons to non-violent delinquents; [17,24]). Examining 1354 serious adolescent offenders from the Pathways to Desistance Study, prior work has demonstrated that only lower IQ and exposure to violence predict having been charged with homicide [25]. Examining retrospective criminal histories of adult male habitual criminals, DeLisi and colleagues demonstrated that juvenile confinement predicted subsequent murder arrests, even upon control of a host of other official criminal offending measures, age of onset, and race/ethnicity [26].…”
Section: Introductionmentioning
confidence: 99%